Artificial Intelligence for the Preservation of Native Languages: The Case of Quechua in Peru - Murrugarra Retamozo, Brenda Isabel (Estudios de Traducción, 2026)
The purpose of this research is to understand the challenges, opportunities, and implications associated with the design and use of Artificial Intelligence (AI) tools to preserve the native Quechua language in Peru. We conducted a theoretical analysis regarding how AI could be applied to protecting Quechua. We also interviewed two Quechua speakers, an expert in the Quechua language, and two experts in ​​language localization and translation. The conclusion was that Quechua is essential to Peruvian identity; however, its preservation faces significant challenges. Although there are laws and government projects to promote it through technology, these have proven ineffective due to a lack of participation from native speakers and engaging content. Therefore, the inclusion of Quechua in AI tools becomes crucial for its intergenerational transmission and for non-speakers to learn the language. However, this requires overcoming the digital divide and the scarcity of linguistic resources. Furthermore, the creation of these tools must guarantee the active participation of communities, protect data sovereignty, and respect cultural diversity. Moreover, AI does not replace social interaction or public policies, so collaborative strategies are needed between the government, the private sector, and organizations that advocate for linguistic rights. Ultimately, success is not measured by the number of applications created, but by their capacity to empower communities and strengthen the everyday use of the language.